MicroRNA-122 Mimic Improves Stroke Outcomes and Indirectly Inhibits NOS2 After Middle Cerebral Artery Occlusion in Rats - Lv, Bo; Cheng, Xiyuan; Sharp, Frank R.; Ander, Bradley P.; Liu, Da Zhi (Frontiers in Neuroscience, 2018)
Aim: Our recent study showed miR-122 mimic attenuated brain infarct volumes, reduced neurological deficits, and decreased NOS2 expression in blood leucocytes after middle cerebral artery occlusion (MCAO) in rats. Since decreasing NOS2 expression alone in leucocytes is insufficient to improve stroke outcomes, we hypothesized that miR-122 mimic may also decrease NOS2 expression in brain microvascular endothelial cells (BMVECs). Methods: We administered PEG-liposome wrapped miR-122 mimic (2.4mg/kg, i.v.) 0 hr or 6 hr after MCAO, and assessed NOS2 expression in BMVECs 24 hr following MCAO in rats. In addition, we used luciferase reporter assays to determine if miR-122 binds to 3’ untranslated regions (3’UTR) of NOS2. Results: We show here that miR-122 mimic (2.4mg/kg, i.v.), given either at 0 hr or 6 hr post MCAO, markedly decreased MCAO-induced NOS2 expression in BMVECs one day following MCAO. However, luciferase reporter assays showed that miR-122 did not bind to 3’UTR of NOS2, suggesting miR-122 knockdown of NOS2 was indirect. Conclusions: These data show the therapeutic efficacy of miR-122 mimic may relate to indirect knockdown of NOS2 in BMVECs and leucocytes.